THE EFFECT OF COGNITIVE APPRENTICESHIP STRATEGY ON DEVELOPING HISTORICAL THINKING SKILLS AMONG EIGHTH GRADE BASIC FEMALE STUDENTS - Ahmed, Qazi Mosa; Ibrahim, Azhar Ali Hussein; Yousif, Falah Faqa (Universitas Muhammadiyah Surakarta, 2025)
This study investigated the effect of cognitive apprenticeship strategy on developing historical thinking skills among eighth-grade students using an experimental design with two equivalent groups. The sample consisted of eighth-grade female students from basic education schools in Zakho during the academic year 2024-2025, randomly assigned to experimental and control groups. The experimental group received instruction based on cognitive apprenticeship strategy while the control group used traditional teaching methods. A historical thinking skills test was developed and validated, encompassing five main skills: chronological and spatial sequencing, historical understanding, thinking about historical evidence, understanding change and continuity, and analyzing historical issues and decision-making. Results revealed statistically significant differences between groups favoring the experimental group, with further analysis showing significant improvement in all historical thinking skills from pre to post-test. Effect size calculations demonstrated that cognitive apprenticeship had a substantial impact on developing students' historical thinking skills. The study recommends incorporating historical thinking skills in social studies curricula and encouraging teachers to implement cognitive apprenticeship strategies.